(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Monitoring of the formation of ultrasmall Cs-AlMCM-41 nanospheres under hydrothermal condition has been performed. It showed that when the CTABr surfactant, silica and alumina were mixed, homogenization of raw materials was first taking place, where CTABr molecules first interacted with the inorganic species via self-assembly into helical rod-like micelles. Hydrolysis, condensation and polymerization of silica and alumina precursors were then initiated. In addition, the Cs+ cation also participated during the formation of MCM-41 structure where it counterbalanced the negative charge of the aluminosilicate surface. After 14 h, the aluminosilicate oligomers were produced and fully enclosed the spherical micelles. Further increasing the hydrothermal treatment to 24 h onwards, polycondensation silanol siloxane would take place leading to the emergence of well-defined and highly ordered MCM-41 structure. This study came up with a clear picture on the formation of Cs-AlMCM-41 hollow nanospheres in cationic-surfactant-templated. This suggested that similar studies for other mesoporous materials such as MCM-48 and MCM-50 under different conditions and approaches could also be explored